The Influence of the Problem Based Learning Model on Students' Critical Thinking and Metacognitive Abilities in Respiratory System Material for Grade XI at SMAN 3 Tebing Tinggi - Chintya Novianti; Ely Djulia (UNIVERSITAS PGRI MADIUN, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on Students' Critical Thinking Skills and Metacognitive Skills on Respiratory System Material in Grade XI. This study uses a Quasi Experimental Design method with a Pretest-Posttest group design. The sampling technique uses Purposive Sampling. The research sample consists of two classes, namely class XI-4 which uses the PBL model and class XI-5 which uses direct instruction learning, each class consisting of 36 students. The instruments in this study are multiple-choice tests of students' critical thinking skills consisting of 30 questions and a questionnaire of students' metacognitive skills consisting of 30 statements. Data were analyzed using prerequisite tests and t-tests (independent sample t-tests). Based on the results of data analysis, there is a significant effect (sig (2-tailed)) <0.05 where 0.000 <0.05 on students' critical thinking skills and metacognitive skills in the experimental class. Based on the results of the hypothesis test, it was found that there was an influence of the PBL model on students' critical thinking skills and metacognitive abilities in the respiratory system material of class XI SMA Negeri 3 Tebing Tinggi.